“A glass half full” or “a breastless dwarf”: Metaphorical talk in women’s accounts of Turner syndrome - Ciepiela, Kamila (LingBaW. Linguistics Beyond and Within, 2024)
This paper examines body-related metaphors used by Polish women to describe lived experiences associated with Turner syndrome (TS), and highlights the contribution this form of analysis can make to the study of health, emotional well-being, and social identity. Turner syndrome is a genetic aberration that affects females, and results in short stature, ovarian failure and a number of less typical body deformations; it often takes a long time to be appropriately diagnosed. Metaphor analysis is employed to analyze a data subset of four semi structured interviews audio recorded and translated from Polish into English. The analysis is carried out with metaphor operationalized as a framing device in discourse, whose main function is to impose a particular axiologically-charged construal of TS. Metaphorical concepts lying at the basis of the metaphors used were identified and grouped into four themes: (i) diagnosis and therapy; (ii) Turner syndrome (iii) appearance (iv) self-esteem and social positioning. The results of the analysis show that a range of composite metaphors develop on the basis of the BODY IS A PHYSICAL OBJECT as a primary metaphor but their occurrence depends on the salience of particular bodily symptoms of TS in individual women. Results are discussed with regard to the function and the utility of metaphor analysis in health, emotional well-being, and social identity research.